How emotional labor leads to turnover intention: the mediating role of job burnout and the moderating role of social support among rural physical education teachers in China - Sun, Pu; Wang, Lifang; Chen, Xi; Cui, Mingyue; Ma, Ke; Yan, Ling (Frontiers in Psychology, 2025)
ObjectiveTo examine the mediating role of job burnout in the relationship between emotional labor strategies and turnover intention among rural physical education (PE) teachers in China, and to explore the moderating effect of social support in this mechanism.MethodsA cross-sectional survey was conducted among 1,761 rural PE teachers using validated self-report scales. Structural equation modeling (SEM) via AMOS 26.0 was used to test the mediating effects of job burnout, followed by moderated mediation analyses using PROCESS macro Model 7, controlling for gender, age, teaching tenure, and education level.ResultsJob burnout significantly mediated the associations between all three emotional labor strategies and turnover intention. Surface acting showed both direct and indirect effects, while deep acting and genuine expression were associated with turnover intention only through burnout. Additionally, social support moderated the relationship between surface acting and burnout, but not for the other two strategies.ConclusionEmotional labor strategies influence turnover intention both directly and indirectly through job burnout, while social support serves as a key buffering resource against the negative impact of surface acting on burnout. These findings underscore the importance of optimizing emotional labor management strategies and strengthening social support networks to enhance teacher wellbeing and promote educational equity in rural schools.